2020
DOI: 10.1128/jvi.02176-19
|View full text |Cite
|
Sign up to set email alerts
|

Salt Enhances the Thermostability of Enteroviruses by Stabilizing Capsid Protein Interfaces

Abstract: Enteroviruses are common agents of infectious disease that are spread by the fecal-oral route. They are readily inactivated by mild heat, which causes the viral capsid to disintegrate or undergo conformational change. While beneficial for the thermal treatment of food or water, this heat sensitivity poses challenges for the stability of enterovirus vaccines. The thermostability of an enterovirus can be modulated by the composition of the suspending matrix, though the effects of the matrix on virus stability ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This finding was indicative that forces other than divalent cation coordination were supporting the organization of such a more complex material. For other types of related protein-only NPs, hydrogen bonds, van der Waals and especially electrostatic interactions were predicted to act, promoting and maintaining protein-protein contacts [23], in a similar way in which monomers are kept together in viral capsids [43][44][45]. In this context, the addition of 0.5% Triton X-100 reduced the size of the materials from more than 100 nm (mean) to 10 nm (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…This finding was indicative that forces other than divalent cation coordination were supporting the organization of such a more complex material. For other types of related protein-only NPs, hydrogen bonds, van der Waals and especially electrostatic interactions were predicted to act, promoting and maintaining protein-protein contacts [23], in a similar way in which monomers are kept together in viral capsids [43][44][45]. In this context, the addition of 0.5% Triton X-100 reduced the size of the materials from more than 100 nm (mean) to 10 nm (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…we demonstrated that cold-chain temperature protects SARS-CoV-2 pseudovirus survival for a long time and decreases the decay rate of the virus compared to exposure in vitro under room temperature. Seawater did not decrease the decay of SARS-CoV-2 pseudovirus in vitro at -18° C, but protected the survival and enhanced the thermostability of SARS-CoV-2 pseudovirus in vitro under the condition of the repeated freeze-thawing cycle, Researchers have shown that salt enhances the thermostability of viruses by increasing van der Waals force and decreasing repulsive electrostatic force (CRAIG WALLIS; Meister et al, 2020; MELNICK)., and could enhance the risk of the SARS-CoV-2 transmission.…”
Section: Resultsmentioning
confidence: 99%
“…The results of freeze−thaw experiments suggest that salt ions in seawater can slow the decay rate of SARS-CoV-2 pseudovirus, but the specific reasons need to be further studied. Researchers have shown that salt enhances the thermostability of viruses by increasing van der Waals forces( Meister et al., 2020 ). Although SARS-CoV-2, with a lipid envelope, is more tolerant to low temperatures than viruses without an envelope ( Yao et al., 2020 ; Isachenko et al., 2021 ), it still can freeze.…”
Section: Discussionmentioning
confidence: 99%